Fully inkjet-printed two-dimensional material field-effect heterojunctions for wearable and textile electronics - Tian Carey (Nature Portfolio, 2017)
Heterojunction structures based on 2D materials show promise for wearable and textile electronics. Here, the authors demonstrate fully inkjet-printed hetero junctions of graphene and h-BN as a platform for FET-based smart electronics on wearable and washable textile substrates.